Health Status and Quality of Life of Dependent Elderly in Thungsong Municipality, Nakhon Si Thammarat Province - Jongrat, Katekanok; Ridchuayrod, Srithaya; Wongmek, Nantawut; Rattanakhot, Nipon (Journal of Health Science of Thailand, 2019)
The objectives of this study were to investigate health status and quality of life of dependent elderly in Thungsong Municipality, Nakhon Si Thammarat. The data collection was performed by using in-depth interview. The sample consisted of 35 caregivers of dependent elderly in Thungsong Municipality, Nakhon Si Thammarat which were selected by using purposive sampling and the data analysis was performed using descriptive statistics and qualitative data analysis. The results showed that most respondents were the merchants aged between 65-69 years (30.4%) with primary school graduates (34.8%) and most primary caregiver were the spouses of the dependent elderly (47.8%). For health status, it was found that the elderly had at least one disease or health problem and the common health problems included high blood pressure, diabetes and so on. For quality of life, it was found that the physical disorders of the elderly were due to aging and lack of health care knowledge which became the causes of chronic diseases. For mental health, it was found that more than 50% of the elderly had mental health problems and were anxious and afraid of being abandoned and alone. For environmental aspect, most of the dependent elderly lived in their own houses rather than living in their children’s houses. For social relations, it was found that when entering old age with unfavorable physical condition for working the elderly might have some problems with socialization or might not participate in any social activities. Changes in the elderly, both physical, mental and social were all affect the quality of life of the elderly.